THE EFFECT OF USING ‘RIDER’ STRATEGY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMPN 42 PEKANBARU IN COMPREHENDING DESCRIPTIVE TEXTS - Gustia, Demi Reka; Purwanti, Indah Tri; Supriusman, Supriusman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The research was aimed to determine the effect of using 'RIDER' strategy on the ability of the second year students of SMPN 42 Pekanbaru in comprehending descriptive texts. This pre-experimental research was conducted by using One-Group Pretest-Posttest design. Class VIII.2 was selected as the sample for this research by using cluster random sampling technique. A multiple choice test consisting of 40 items was the instrument of the research. The collected data were analyzed by using t-test. The results showed that the mean score of post-test was higher than pre-test (74.24>61.84). Then, it also showed that t-test was higher than t-table (4.086>2.062) at a significance level of 5%. Therefore, Alternative Hypothesis (Ha) is accepted and Null hypothesis (Ho) is rejected. It can be concluded that there is a significant effect of ‘RIDER’ Strategy on the ability of the second year students of SMPN 42 Pekanbaru in comprehending descriptive texts.Keywords: Reading, Reading Comprehension, Descriptive Text, ‘RIDER’ Strategy